Physicochemical analysis and treatment of tube well water in UiTM Pahang Branch - Ab Manan, Wan Noni Afida; Mohd Ashri, Nik Syaiful Ashraf; Mokhtar, Hamizah; Ismail, Noorul Najwa Iqhlima; Tholibon, Duratul Ain; Ayob, Afizah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
Tube well water is one of the groundwater supplies for human consumption. However, most of the groundwater quality is unfit for human use without proper treatment. This research work intends to evaluate the physicochemical properties of groundwater samples, to determine heavy metal concentrations in groundwater samples and to apply the membrane filtration method to treat the groundwater samples. A total of 48 bottles of samples were collected from four sources (Points A, B, C, and D) of the tube well system in UiTM Pahang branch. Temperature, pH, dissolved oxygen (DO), total dissolved solids (TDS), conductivity, total suspended solids (TSS) and turbidity are some of the physical and chemical characteristics of tube well water that have been identified. Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) was used to measure the levels of heavy metals. Findings indicate that most physicochemical readings are below the permissible limit. Mn and Fe metals show the above limit by the WHO before membrane filtration. The highest percentage of Fe (98.75%) is removed by membrane filtration, followed by the percentages of Cd (97.14%), Cu (96.43%), and Mn (94.89%). In addition, about 65.22% of Pb and 61.29% of Zn can be eliminated with membrane filtration. In conclusion, the results of this study serve as a guide for the quality of groundwater from tube wells that can be used for human purposes, including drinking, farming, and industry.